The archaeology of cremation: burned human remains in funerary studies - Thompson, Timothy James Upton (Studies in funerary archaeology, 2015)
"There is a considerable body of knowledge on the concepts and practices of inhumation yet our understanding of cremation ritual and practice is by comparison, woefully inadequate. This volume draws together the inventive methodology that has been developed for this material and combines it with a fuller interpretation of the archaeological funerary context. It demonstrates how an innovative methodology, when applied to a challenging material, can produce new and exciting interpretations of archaeological sites and funerary contexts. The reader is introduced to the nature of burned human remains and the destructive effect that fire can have on the body. Subsequent chapters describe important cremation practices and sites from around the world and from the Neolithic period to the modern day. By emphasising the need for a robust methodology combined with a nuanced interpretation, it is possible to begin to appreciate the significance and wide-spread adoption of this practice of dealing with the dead"--Provided by publisher